Not without laughter - Hughes, Langston, 1902-1967 (Penguin classics., 2018)
Our greatest African American poet's award-winning first novel, about a black boy's coming-of-age in a largely-white Kansas town. When first published in 1930, Not Without Laughter established Langston Hughes as not only a brilliant poet and leading light of the Harlem Renaissance but also a gifted novelist. In telling the story of Sandy Rogers, a young African American boy in small-town Kansas, and of his family--his mother, Annjee, a housekeeper for a wealthy white family; his irresponsible father, Jimboy, who plays the guitar and travels the country in search of employment; his strong-willed grandmother Hager, who clings to her faith; his Aunt Tempy, who marries a rich man; and his Aunt Harriet, who struggles to make it as a blues singer--Hughes gives the longings and lineaments of black life in the early twentieth century an important place in the history of racially divided America. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,800 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.